Determination of Chloride Ion in Selenium(IV) System with Silver-Diethyldithocarbamate Modified Electrode - Zhao, Shi-hao; Zhang, Ping-Ping; Chen, Li-Yan (Asian Journal of Chemistry, 2010)
The silver-diethyldithocarbamate (DDTC Ag) modified electrode was constructed and a new method for the determination of chloride ion has been established at the modified electrode. The results indicated that a well-defined stripping peak were obtained at DDTC Ag modified electrode by the anodic stripping voltammetry technique and the addition of Se(IV) can further increase the sensitivity. In addition, the experiment parameters such as buffer pH, the concentration of Se(IV), accumulation potential and accumulation time were optimized. Under the selected conditions, the oxidation peak currents were in linear with concentration of chloride ion in the range of 1 × 10-4 – 8 × 10-3 mol L-1 (R = 0.9992). Detection limit of it reached 2 × 10-5 mol L-1. The method could obtain better result when it applied to the determination of chloride ion in soy.